Negosiasi Identitas dan Kebutuhan pada Ruang Publik bagi Jemaah Perempuan Salafi Masjid Abu Bakar Shiddiq di Deli Serdang - Habibina Menatri; Neila Susanti; Rholand Muary (Journal of Religion and Social Transformation, 2025)
This article examines the process of religious identity negotiation undertaken by Salafi women in relation to their need for public space at the Abu Bakar Shiddiq Mosque in Deli Serdang. It highlights how religious groups known for their strict understanding of women's roles in the domestic sphere often face social challenges due to their presence in public spaces. Their involvement in public spaces continues through study groups, children's education, and social activities. This research uses a qualitative method with a phenomenological approach, collecting data through participatory observation, field notes, literature review, and interviews. The findings show that Salafi women negotiate their identity by adhering to the principles of manhaj, such as wearing sharia-compliant clothing, regulating the timing of activities, and limiting interaction with non-mahram men. This study emphasizes that the mosque not only functions as a center of worship but also as a social arena that allows Salafi women to maintain their religious identity, thereby contributing to the study of the sociology of religion by highlighting that Salafi women are not only passive but also actively negotiate to bridge religious values and social space needs.